Parametric sensitivity of pH and steady state multiplicity in a continuous stirred tank bioreactor (CSTBR) using a lactic acid bacterium (LAB), Pediococcus acidilactici. Issue 5 (22nd June 2015) - Das, Subhashis; Banerjee, Aritro; Chowdhury, Ranjana; Bhattacharya, Pinaki; Calay, Rajnish Kaur
Abstract: BACKGROUND: A continuous stirred tank bioreactor (CSTBR) represents an open dynamic system with high probability to show nonlinear behavior such as parametric sensitivity and multiplicity of steady state. A priori determination of this behavior is needed to decide on the strategy of reactor operation. RESULTS: The growth of a lactic acid bacterium, namely, Pediococcus acidilactici in a 2 L CSTBR is used to demonstrate the existence of parametric sensitivity of pH and the multiplicity of steady state in the system. A mathematical model has been developed and a dimensionless multiplicity criterion, ω, has been derived to indicate the set of values of input parameters corresponding to multiple steady states. Experiments have been conducted to study parametric sensitivity of pH with respect to input variables, namely, dilution rates and concentrations of nutrient and alkali stream for pH control in the regions of multiple and unique steady states. The CSTBR exhibited parametric sensitivity of pH over the entire region of operation under study. The experimental trends of parametric sensitivity of pH are also in agreement with those of theoretical parametric sensitivity of pH. CONCLUSION: The nonlinear behavior of a CSTBR has been thoroughly portrayed in this article. The present study will add to the knowledge of control and operational strategies of CSTBRs. © 2015 Society of Chemical Industry